A taste of temptation ebook - Grey, Amelia (Terrible Threesome., 2014)
She Came to Avoid a Scandal Olivia Banning came to London to solve one mystery, and stumbled upon another quite by accident. Unfortunately her plans are disrupted when the notoriously rakish Earl of Dugdale catches her investigating—in his bedchamber. And Ended Up the Talk of the Ton Andrew Terwillger, the Earl of Dugdale, scoffs at Olivia's tales of things that go bump in the night, although her beauty and courage are tempting. When they're caught in a kiss, neither he nor she wants the marriage Society demands. But marry they must, despite their misgivings. And as soon as they say "I do," increasingly strange and mysterious things start to happen... Praise for The Rogue Steals a Bride: "An enchanting romance."—RT Book Reviews, 4 ½ stars "Devilishly charming...A touching tale of love conquering misplaced honor."—Library Journal "Sensual and touching...Witty and clever...Another great story of forbidden love."—Fresh Fiction